Strategi Kebijakan Luar Negeri Indonesia dalam Menghadapi Tuberkulosis sebagai Ancaman Keamanan Manusia - Silky Adhitya Agustina Nugroho; Abil, Nabila Zahira (Jurnal Transformasi Global, 2026)
This study analyzes Indonesia’s foreign policy  strategy for addressing tuberculosis (TB), a disease that has evolved from a domestic health concern into a threat to human and cross-border security. As a country with one of the highest rates of TB in the world, Indonesia faces threats to its socio-economic stability, hindered SDG progress, and undermined individual security. Indonesia employs health diplomacy as a strategic instrument to promote human security and strengthen its global position. This strategy is evident through its active participation in multilateral forums, such as the UN, and its compliance with the WHO's End TB Strategy, as outlined in Presidential Regulation No. 67 of 2021. Through international cooperation, Indonesia mobilizes global resources, advocates for equitable access to health services, and acts as a normative pioneer. This approach, in line with liberal institutionalism, explains Indonesia's use of international cooperation through the End TB Strategy to address TB as a threat to human security.